Upper age limit for assisted reproductive technologies: Ethics opinion - Sujata Kar; Duru Shah; Madhuri Patil (Wolters Kluwer Medknow Publications, 2018)
Fertility in women is closely related to reproductive age and becomes significantly compromised before the onset of perimenopausal menstrual irregularity. There is decrease in oocyte quality with age which is reflected by the increase of chromosomal aberrations in the oocytes and embryos. Oocyte or embryo donation to women of advanced age should be discouraged.